Transdermal Delivery and Biological Activity of Arginine Oligomer Conjugation of Palmitoyl Tripeptide-1 - Park, Su In; Lee, Kwang Won; Park, Shinsung; Shin, Moon Sam (International Journal of Innovative Research and Scientific Studies, 2022)
GHK is a promising cosmeceutical peptide that stimulates the synthesis of ECM and modulates the activity of Matrix Metallo Proteinases (MMPs). However, due to the hydrophilic properties of GHK, skin permeability is a challenge. To overcome this limitation, we considered two peptide modifications, namely palmitoyl attachment and arginine oligomer conjugation. First, we evaluated the optimal modification of GHK for skin penetration using the Franz diffusion cell assay with 3D human reconstructed skin. We found that skin permeability was slightly increased by attaching palmitoyl at the N-terminus of GHK, while it was significantly increased by conjugating arginine oligomers at the C-terminus of GHK. In the comparison between R4, R6, and R8, R4 showed the highest penetrating potential, and the permeability of Pal-GHK-R4 was about 7-fold higher than that of GHK. Based on the skin permeability results, the optimal peptide, Pal-GHK-R4, was synthesized using SPPS, after which its biological activities were verified. Evaluating MMP-2 activity by gelatin zymography and collagen production by Sircol collagen assay showed that Pal-GHK-R4 had approximately100-fold lower active concentrations than GHK. In other words, we established the novel peptide Pal-GHK-R4 as a modification that significantly increases both the biological activities and skin permeability of GHK.